2021
DOI: 10.1186/s12863-021-00961-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of brown marmorated stink bug, Halyomorpha halys based on mitochondrial COI and COII haplotypes

Abstract: Background In the past decade, the brown marmorated stink bug (BMSB), Halyomorpha halys (Hemiptera: Pentatomidae) has caused extensive damage to global agriculture. As a high-risk pest for many countries, including New Zealand, it is important to explore its genetic diversity to enhance our knowledge and devise management strategies for BMSB populations. In this study, two mitochondrial genes, Cytochrome c oxidase I (COI) and Cytochrome c oxidase II (COII) were used to explore the genetic diver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…The continued and consistent detection of one or more of these same haplotypes in Europe following the initial invasion (e.g. H1, H3, H8 and H33; Cesari et al 2015Cesari et al , 2018Gariepy et al 2015;Morrison et al 2017;Šapina and Jelaska 2018;Schuler et al 2020;Yan et al 2021), largely supports the occurrence of a bridgehead effect, wherein particularly successful invasive populations have given rise to secondary invasions in other locations (Lombaert et al 2010;Lawson Handley et al 2011). However, in Italy and Greece, subsequent introductions directly from Asia may have also taken place between 2013 and 2019, as a combined total of 20 additional haplotypes (including 14 previously undescribed haplotypes) have been reported in more recent studies in these two countries (Morrison et al 2017;Cesari et al 2018;Schuler et al 2020).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The continued and consistent detection of one or more of these same haplotypes in Europe following the initial invasion (e.g. H1, H3, H8 and H33; Cesari et al 2015Cesari et al , 2018Gariepy et al 2015;Morrison et al 2017;Šapina and Jelaska 2018;Schuler et al 2020;Yan et al 2021), largely supports the occurrence of a bridgehead effect, wherein particularly successful invasive populations have given rise to secondary invasions in other locations (Lombaert et al 2010;Lawson Handley et al 2011). However, in Italy and Greece, subsequent introductions directly from Asia may have also taken place between 2013 and 2019, as a combined total of 20 additional haplotypes (including 14 previously undescribed haplotypes) have been reported in more recent studies in these two countries (Morrison et al 2017;Cesari et al 2018;Schuler et al 2020).…”
Section: Introductionmentioning
confidence: 89%
“…The mitochondrial Cytochrome Oxidase I (COI) gene has shown utility in species identification and separation of genetic lineages (Bucklin et al 2011;Stephens et al 2011), in particular as it relates to reconstructing routes of invasion (Auger-Rozenberg et al 2012;Chapman et al 2015). Although the Cytochrome Oxidase II (COII) gene of H. halys has also been sequenced (Xu et al 2014;Cesari et al 2015Cesari et al , 2018Yan et al 2021), the COI gene has been used more extensively in the characterisation of the invasion history, diversity and identity of H. halys haplotypes in both native and invaded regions (Gariepy et al 2014(Gariepy et al , 2015Cesari et al 2015Cesari et al , 2018Zhu et al 2016;Morrison et al 2017;Valentin et al 2017;Lee et al 2018;Horwood et al 2019;Schuler et al 2020;Yan et al 2021). Based on the COI haplotype analysis of H. halys, it has been suggested that multiple invasion events took place in the initial / early stages of invasion in Europe (2007)(2008)(2009)(2010)(2011)(2012), with the population in Switzerland (primarily haplotype H3 and H8) resulting from the establishment of individuals that arrived directly from China; the population in Italy (primarily H1) resulting from the establishment of individuals from the invasive population in the USA; and the population in Greece (predominantly haplotype H33) resulting from a separate establishment of H. halys from China (Cesari et al 2015;Gariepy et al 2015;Valentin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations